Active Citizenship among the Youth: Differences among Sangguniang Kabataan Leaders and Their Constituents - Alampay, Erwin Gaspar A.; Angeles, Lydia E. (Philippine Journal of Public Administration; Vol 56 No 2 (2012), 2017)
This article is based on results of a pilot baseline survey among Sangguniang Kabataan (SK) leaders and youth in Quezon City. The research builds on previous research done by the Center for Leadership, Citizenship and Democracy (CLCD) on mobilizing for active citizenship, on assessing the performance of the Sangguniang Kabataan, and on citizenship in general. The survey instrument was developed based on the citizenship questionnaire that was administered by and combined with the work done on civic engagement at the Center for Information and Research on Civic Learning and Engagement (CIRCLE) and research by Flanagan and Torney-Purta. Fifty-one respondents participated in the pilot (SK leaders = 21, non-SK youth = 30), with ages ranging between 15 and 19. The mean age of the SK leaders (SK = 17.3) is higher than that of the non-SK respondents (15.5). Mean tests show that SK leaders are significantly more engaged in the community (e.g. doing  community service, contacting a public official, signing a petition, voted, volunteered with environmental organizations), and rated themselves significantly higher as a citizen as a result. However, much of this engagement may be a factor of the opportunities afforded to them because of their position. The results suggest that SK leaders still need to be taught alternative ways for engagement, beyond their roles as SK leaders. The bigger challenge remains on how SK leaders can encourage the ordinary youth to volunteer, participate and be more active in the community.
Keywords: citizenship, active citizenship, civic-engagement, Sangguniang Kabataan (SK)